Implementasi Zakat Pertanian Perpekstif Ekonomi Islam: (Studi kasus di Dusun Rokoning dan Dusun Sambih Tanah Merah Dajah) - Dewi Hidayati; Rahmat Rahmat; Susanti Susanti (Journal of Economic and Islamic Research, 2023)
This study aims to determine the implementation of agricultural zakat from the perspective of Islamic economics in Rokoning and Sambih hamlets. This type of research is field research with a qualitative descriptive method. Taking purposive sampling. With the data collection method of interviews, observation, and documentation. The results of the study show that the implementation of agricultural zakat in Rokoning and Sambih hamlets is generally carried out but in practice, it is not by Islamic law. Because the traders there do not know the procedures for implementing agricultural zakat. Starting from the obligatory conditions of zakat, its distribution, nisab, haul, and the levels of zakat on agricultural assets. Viewed based on Islamic economics in general it is not by the rules of Islamic economics. This is because the farmers in carrying out their agricultural zakat do not use the laws that have been established for agricultural zakat. There are even those who equate the concept of this trade with alms. However, among them, some carry it out correctly and by the rules of Islamic law.